Building Bridges in a Divided Society: Addressing Hindutva and Muslim Conflicts in India - Mehmet Masatoğlu (Marifetname)

(untitled)
The purpose of this research is to perform a comprehensive investigation of the complex dynamics that exist between Hindutva and the Muslim minority in India, with a particular emphasis on the conflict that is becoming more intense. It investigates the complicated situation by delving into the myriad of political, religious, and sociological aspects that interact with one another and contribute to shaping it. This research investigates the purposeful aggravation of racial discrimination, nationalism, and exclusionary policies that have a disproportionate impact on the Muslim population in India, which is a minority population. The research draws from a wide variety of scholarly sources. As an additional benefit, it gives light on the politicization of Hinduism within the public sphere of India. Additionally, it explores the rise and spread of Hindu nationalism while simultaneously evaluating the corresponding socio-political issues that are encountered by the Muslim minority. This study highlights the urgent need for a narrative that fights for inclusion, secularism, and progressiveness while also embracing diversity. This is accomplished through an examination that encompasses historical Hindu-Muslim debates, media depictions, and government policies. In addition to this, it investigates the negative effects that arose as a result of Islamophobia, socio-spatial segregation, and state-driven oppression, particularly in light of current changes in Indian politics. Within the scope of this investigation, a critical analysis of the role that the state plays, particularly with regard to its preference for some religious groups over others, is an essential component. In addition, this research investigation examines a number of different strategies with the objective of reducing disputes between different groups and promoting interfaith communication, mutual respect, and peaceful coexistence. The main goal is to create a society that is welcoming to people of all religious backgrounds, one in which members of other faiths are able to freely practice their faith without fear of being discriminated against or punished. It is important to note that this research continually highlights the necessity of open and constructive conversation, policy changes, and balanced media portrayal in the process of revising the dominant narrative. The fundamental objective of this initiative is to foster a conversation that emphasizes the utmost significance of social justice, equality, and inclusion within the framework of the modern-day India.